Results and performance of the World Bank Group 2012 - Dittbrenner, Heather (Independent Evaluation Group Studies, 2013)
The World Bank Group has made important contributions to poverty reduction in developing countries. But to stay relevant under the uncertain conditions that characterize today?s global development context, the Bank Group needs to enhance its capacity to help clients cope with weak economic growth, address persistent disparities in development progress, and manage the increasingly global and cross-cutting nature of development solutions. The messages in this report from the Independent Evaluation Group (IEG) seek to help the Bank Group improve its programs and development outcomes. Thus the primary audience is Bank Group management. Additional audiences include other development organizations, nongovernmental organizations, and civil society organizations that are involved in development issues, as they also seek better development outcomes. This report addresses IEG's work over the last year, summarizing findings from its evaluations and discussing the trends that are revealed. In particular, as a consequence of the Bank Group's rapid, large-scale response to the 2008?09 crisis, the Bank?s remaining capital headroom precludes a comparable expansion should another crisis occur. In addition, the extent to which country programs meet their objectives has yet to reach the performance target set in the Bank?s Corporate Scorecard. Development outcome ratings of Bank-funded investment projects, as well as the outcome ratings for International Finance Corporation (IFC) investments, have recently declined. IEG?s findings suggest that enhancing the quality of projects at their outset as well as their supervision would help reverse the decline in Bank project ratings; along the same line, improving IFC?s work quality would strengthen the results of its investments. Evaluation evidence also underscores the importance of sustained dialogue with stakeholders and of high-quality analytical work to sharpen the understanding of client circumstances, which is essential for successful outcomes. Effective development solutions require intensified efforts by the Bank Group to work across conventional boundaries.